Reflected Knowledge and Trust in Global Collaboration - Mortensen, Mark; Neeley, Tsedal B. (Management Science, 2012)
Scholars argue that direct knowledge about distant colleagues is crucial for fostering trust in global collaboration. However, their arguments focus mainly on how trust accrues from knowledge about distant collaborators' personal characteristics, relationships, and behavioral norms. We suggest that an equally important trust mechanism is “reflected knowledge,” knowledge that workers gain about the personal characteristics, relationships, and behavioral norms of their own site through the lens of their distant collaborators. Based on surveys gathered from 140 employees in a division of a global chemical company, we found that direct knowledge and reflected knowledge enhanced trust in distinct ways. Although both enhanced feelings of closeness with others, results indicate that direct knowledge increased focal actors' understanding of their distant colleagues, whereas reflected knowledge promoted feelings of being understood. We discuss implications of reflected knowledge to theories of trust and interpersonal dynamics in globally distributed collaboration. This paper was accepted by Jesper Sørensen, organizations.